2012
DOI: 10.1097/hjh.0b013e3283531eaf
|View full text |Cite
|
Sign up to set email alerts
|

Home versus ambulatory and office blood pressure in predicting target organ damage in hypertension

Abstract: These data suggest that home BP is as good as ambulatory monitoring and superior to office measurements in regard to their association with preclinical organ damage assessed by echocardiographic LVMI. More research is required to evaluate the relationship of home BP with other indices of target organ damage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
130
0
30

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 245 publications
(165 citation statements)
references
References 43 publications
5
130
0
30
Order By: Relevance
“…ABP measurements are more closely related to subclinical target organ damage (TOD) (6, 7) and a risk of cardiovascular events (8,9). Other reports also suggested that HBP is useful in predicting hypertension-induced TOD, and is superior to carefully taken OBP measurements (10).…”
Section: Introductionmentioning
confidence: 99%
“…ABP measurements are more closely related to subclinical target organ damage (TOD) (6, 7) and a risk of cardiovascular events (8,9). Other reports also suggested that HBP is useful in predicting hypertension-induced TOD, and is superior to carefully taken OBP measurements (10).…”
Section: Introductionmentioning
confidence: 99%
“…Prognostyczne znaczenie ciśnienia tętniczego w pomiarze ambulatoryjnym. W kilku badaniach wykazano, że u pacjentów z nadciśnieniem tętniczym przerost lewej komory (LVH), zwiększona grubość błony wewnętrznej i środkowej (IMT) w tętnicy szyjnej oraz inne wskaźniki powikłań narządowych korelują ściślej z BP w pomiarze ambulatoryjnym niż z BP mierzonym w gabinecie lekarskim lub w przychodni [82,83]. Ponadto udowodniono, że średnie BP w ciągu całej doby wykazuje silniejszy związek z chorobowością i umieralnością niż BP mierzone w warunkach klinicznych [84][85][86][87].…”
Section: Pomiary Ciśnienia Tętniczego Poza Gabinetem Lekarskim Lub Prunclassified
“…Ciśnienie tętnicze w warunkach domowych wykazuje ściślejszy związek z powikłaniami narządowymi nadciśnienia, w tym zwłaszcza z LVH [82,83], niż BP mierzone w gabinecie lekarskim lub w przychodni. Niedawne metaanalizy kilku prospektywnych badań przeprowadzonych w populacji ogólnej, w podstawowej opiece zdrowotnej, oraz u pacjentów z nadciśnieniem tętniczym wskazują, że zdolność przewidywania chorobowości i umieralności z przyczyn sercowo-naczyniowych na podstawie BP w pomiarach domowych jest istotnie lepsza w porównaniu z BP mierzonym w warunkach klinicznych [102,103].…”
Section: Prognostyczne Znaczenie Domowych Pomia-unclassified
See 1 more Smart Citation
“…2 However, HBPM is underused in primary care. 3,4 Home blood pressure measurement is a better predictor of cardiovascular disease outcomes 2,5 and target organ damage 5,6 than blood pressure measured in a physician's office. HBPM is an evidence-based strategy that has been shown to lower blood pressure, 2,7-11 improve medication adherence, 2,12,13 and promote lifestyle changes to improve blood pressure control.…”
mentioning
confidence: 99%